2021
DOI: 10.3390/nu13030950
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Mechanism of Curcumin on Human Glioblastoma

Abstract: Glioblastoma (GBM) is the most malignant brain tumor and accounts for most adult brain tumors. Current available treatment options for GBM are multimodal, which include surgical resection, radiation, and chemotherapy. Despite the significant advances in diagnostic and therapeutic approaches, GBM remains largely resistant to treatment, with a poor median survival rate between 12 and 18 months. With increasing drug resistance, the introduction of phytochemicals into current GBM treatment has become a potential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 160 publications
0
42
0
Order By: Relevance
“…Curcumin is the major active component in turmeric ( Curcuma longa ), a commonly used spice and coloring food additive [ 66 ]. It is one of the most investigated natural products with regard to anticancer activity knowing to regulate miRNA expression and modifying a series of signaling pathways in various types of cancer (e.g., endometrial cancer or human glioblastoma) [ 67 , 68 , 69 ]. With regard to MM, curcumin has been investigated for its effect on U266, MM1S, MM1R, and RPMI8226 cell lines and completely suppressed cell proliferation at a concentration of 10 µM [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin is the major active component in turmeric ( Curcuma longa ), a commonly used spice and coloring food additive [ 66 ]. It is one of the most investigated natural products with regard to anticancer activity knowing to regulate miRNA expression and modifying a series of signaling pathways in various types of cancer (e.g., endometrial cancer or human glioblastoma) [ 67 , 68 , 69 ]. With regard to MM, curcumin has been investigated for its effect on U266, MM1S, MM1R, and RPMI8226 cell lines and completely suppressed cell proliferation at a concentration of 10 µM [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, activated (i.e., non-phosphorylated) Rb binds to chromatin and prevents cell cycle progression by inhibiting the E2F target transcription [21]. E2F target genes encode signals essential for DNA replication and nucleotide biosynthesis, thus promoting cell growth [19,22].…”
Section: Rb Pathway (Retinoblastoma)mentioning
confidence: 99%
“…Crosstalk between glioma cells and cellular components of tumor milieu like TAMs and TANs modulates the activity of signaling pathways, which eventually promote cancer progression, tumor cell migration and invasion, and immune suppression. Some of the key pathways (Figure 2) that are activated during oncogenic events include nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), Janus kinase-signal transducer and activator of transcription (JAK/STAT), mitogen-activated protein kinase (MAPK), phosphatidylinositol-3-kinase and the mammalian target of rapamycin (PI3K/Akt/mTOR), and Toll-like receptors (TLRs) [92][93][94][95]. Further discussion focuses on the key signaling transduction pathways that are activated during the inflammatory process and involved in GBM pathogenesis.…”
Section: Signal Transduction Pathways Involved In Glioma Progressionmentioning
confidence: 99%
“…The increased activity of pro-inflammatory, angiogenic, and anti-apoptotic proteins has been linked with NF-κB activation in glioma [92]. Several studies have shown elevated NF-κB activity in different GBM models [95,102]. TGF-β has been found to upregulate miR-182 in order to prolong NF-κB activation in GBM specimens [103].…”
Section: Nf-κb Signaling Pathwaymentioning
confidence: 99%